Healthy People Mall Development: Promotive and Preventive Service of Public Health Center during the Covid-19 Pandemic - Prayoga, Diansanto; Fatah, Mohammad Zainal; Sari, Jayanti Dian Eka; Rahayu, Ajeng Febrianti; Lailiyah, Syifa’ul (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Healthy People Mall (Mall Orang Sehat/MOS) is a health service facility at the Public Health Center and its network that provides promotive and preventive service with the purpose of a healthy community. The COVID-19 pandemic has some impacts on all sectors of life, including the implementation of the MOS program. This study aimed to develop the Healthy People Mall as a promotive and preventive service of the Public Health Center during the COVID-19 pandemic in Banyuwangi Regency. This was an observational study with a survey approach conducted in the Public Health Center working areas. The number of samples obtained in this study were 389 consisting of adult communities who utilized the Public Health Center. The result of the study showed that the community learned about the MOS program through banners. The majority of the services that were utilized by the community was health promotion. The COVID-19 has an impact on the accessibility of MOS which can be seen from the drastic decline in the number of visits. Another impact of the COVID-19 pandemic was the increasing frequency of accessing the internet by the respondents. MOS development is necessary to be carried out that it can still provide safe and comfortable service, and do not harm each other.